FabLab : of machines, makers and inventors - Walter-Herrmann, Julia, ....-; Büching, Corinne, ....- (Bielefeld : transcript Verlag, 2013)
Ten years after the first FabLab (a so called fabrication laboratory) was opened at MIT, more than 120 FabLabs exist all over the world. Today, it is time to look back at a decade of FabLab activities. This book shows how small production devices, such as laser cutters and 3D printers, and dedicated educationists, researchers and FabLab practitioners transform the fields of learning, work, production, design, maker culture, law and science on a global scale. In this composition experts from various countries, such as Germany, India or the USA, and distinguished academic institutions, such as MIT or Stanford University, discuss theoretical questions and introduce practical approaches concerning FabLab activities.